Six-Year Follow-Up Outcomes of Catheter Ablation of Para-Hisian Accessory Pathways - Chen, Qingxing; Xu, Lili; Zou, Tian; Cheng, Kuang; Ling, Yunlong; Xu, Ye; Pang, Yang; Liu, Guijian; Zhu, Wenqing; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Background: Ablation of para-hisian accessory pathways (APs) remains challenging due to anatomic characteristics and few studies have focused on the causes for recurrence of radiofrequency ablation of para-hisian APs. Objective: This retrospective single center study was aimed to explore the risk factors for recurrence of para-hisian APs. Methods: 113 patients who had para-hisian AP with an acute success were enrolled in the study. In the 6-year follow-up, 15 cases had a recurrent para-hisian AP. Therefore 98 patients were classified into success group while 15 patients were classified into recurrence group. Demographic and ablation characteristics were analyzed. Results: Gender difference was similar in two groups. The median age was 36.2 years old and was younger in recurrence group. Maximum ablation power was significantly higher in success group (29±7.5 vs 22.9±7.8, p<0.01). Ablation time of final target sites was found to be markedly higher in success group (123.4±53.1 vs 86.7±58.3, p<0.05). Ablation time less than 60 seconds was detected in 12 (12.2%) cases in success group and 7 (46.7%) cases in recurrence group (p<0.01). Occurrence of junctional rhythm was significantly higher in recurrence group (25.5% vs 53.3%, p<0.05). No severe conduction block, no pacemaker implantation and no stroke were reported. Junctional rhythm during ablation (OR=3.833, 95%CI 1.083-13.572, p=0.037) and ablation time <60s (OR=5.487, 95%CI 1.411-21.340, p=0.014) were independent risk factors for the recurrence of para-hisian AP. Conclusions: With careful and accurate mapping, it is relatively safe to ablate para-hisian AP. If possible, proper extension of ablation time could reduce the recurrence rate of para-hisian APs.